Assessing the Validity of the 12th Grade Ministerial Exam of English Language in Kurdistan - Mustafa, Awat; Azeez, Nadhim; Ahmad, Rawand (Academic Journal of Nawroz University, 2022)
It has been almost a decade that the format of 12th grade ministerial exam questions has been changed to Multiple Choice Questions (MCQ). It has been claimed that language tests have to reflect what learners study in the class during the process of learning. It is the aim of this study to investigate the validity of the 12th ministerial exanimation in the light of the communicative language approach (CLA). For this purpose, the researchers designed a questionnaire for 100 freshly graduates of the 12th grade learners from Kurdistan Region schools. The overall results show that the test doesn’t follow the CLA testing principles. In addition, more than %85 of the learners reported that they had learned little English during their study year, and they mostly study on their teachers’ pamphlets rather than the course book. Nevertheless, the 12th grade learners are generally satisfied with the format of the ministerial examination of English and think that question items are easy to answer.